Genetic Homozygosity and Phenotypic Variability in Craniosynostotic Rabbits. (January 2017) - Gilbert, James R.; Cray, James J.; Kreithen, Amy; Marazita, Mary L.; Cooper, Gregory M.; Losee, Joseph E.; Siegel, Michael I.; Mooney, Mark P.
Background: Craniosynostosis ranges in severity from single suture involvement with prenatal onset to multiple suture involvement with postnatal onset. The present study was designed to test the hypothesis that increasing homozygosity may be responsible for more severe phenotypic expression by examining the relationship between inbreeding and phenotypic expression in synostotic rabbits. Methods: Data were obtained from 173 litters and 209 rabbits with familial craniosynostosis. Five distinct phenotypes were identified (normal n = 62; unicoronal delayed onset synostosis (DOS) n = 47; bicoronal DOS n - 21; unicoronal early onset synostosis (EOS) n - 26, and bicoronal EOS n = 53). Wright's coefficients of inbreeding (CI) were calculated using CompuPed software. Radiographs were taken at 10, 25, 42, 84, and 126 days of age to assess coronal suture, craniofacial, and skeletal growth. The relationship between CI and growth data was assessed using correlation coefficients. Results: Mean CIs ranged from 15.68 (±2.22) in normal rabbits to 25.89 (±5.03) in bicoronal DOS, to 36.29 (±2.10) in unicoronal EOS to 42.85 (±2.10) in bicoronal EOS rabbits. Significant differences were noted among groups (F - 11.48; P < .001). Significant negative correlations were noted between CI and sutural and craniofacial growth at 25 (r = -.45, P < .001; and r = -.66, P < .001) through 126 (r = -.40, P < .001 and r = -.46, P < .001) days of age. Conclusions: While the synostotic phenotype is inherited in an autosomal dominant fashion in these rabbits, increasing homozygosity is associated with more severely affected phenotypes. These findings suggest that an accumulation of additional, modifier genes may determine the severity of the synostotic phenotype in rabbits.